SN 2020uem: a Possible Thermonuclear Explosion within a Dense Circumstellar Medium. I. The Nature of Type IIn/Ia-CSM SNe from Photometry and Spectroscopy - Uno Kohki; Maeda Keiichi; Nagao Takashi; Nakaoka; Tatsuya; Motohara Kentaro; Tajitsu Akito; Konishi Masahiro; Koyama Shuhei; Takahashi; Hidenori; Tanaka; et al. (Institute of Physics, 2025)
We have performed intensive follow-up observations of a Type IIn/Ia-CSM supernova (SN IIn/Ia-CSM), 2020uem, with photometry, spectroscopy, and polarimetry. In this paper, we report on the results of our observations focusing on optical/near-infrared (NIR) photometry and spectroscopy. The maximum V-band magnitude of SN 2020uem is less than −19.5 mag. The light curves decline slowly with a rate of ∼0.75 mag/100 days. In the late phase (≳300 days), the light curves show accelerated decay (∼1.2 mag/100 days). The optical spectra show prominent hydrogen emission lines and broad features possibly associated with Fe-peak elements. In addition, the Hα profile exhibits a narrow P-Cygni profile with an absorption minimum of ∼100 km s−1. SN 2020uem shows a higher Hα/Hβ ratio (∼7) than those of SNe IIn, which suggests a denser circumstellar medium (CSM). The NIR spectrum shows the Paschen and Brackett series with a continuum excess in the H and Ks bands. We conclude that the NIR excess emission originates from newly formed carbon dust. The dust mass (Md) and temperature (Td) are derived to be (Md, Td) ∼ (4−7 × 10−5 M⊙, 1500–1600 K). We discuss the differences and similarities between the observational properties of SNe IIn/Ia-CSM and those of other SNe Ia and interacting SNe. In particular, spectral features around ∼4650 Å and ∼5900 Å of SNe IIn/Ia-CSM are more suppressed than those of SNe Ia; these lines are possibly contributed, at least partly, by Mg i] and Na i, and may be suppressed by high ionization behind the reverse shock caused by the massive CSM.